Valuing Nature Waste Removal in the Offshore Environment Following the Deepwater Horizon Oil Spill - Washburn, Travis W.; Yoskowitz, David W.; Montagna, Paul A. (Frontiers in Marine Science, 2018)
The offshore and deep-sea marine environment provides many ecosystem services (i.e., benefits to humans), for example: climate regulation, exploitable resources, processes that enable life on Earth, and waste removal. Unfortunately, the remote nature of this environment makes it difficult to estimate the values of these services. One service in particular, waste removal, was examined in the context of the Deepwater Horizon oil spill. Nearly 5 million barrels of oil were released into the offshore Gulf of Mexico, and 14 billion dollars were spent removing about 25% of the oil spilled. Using values for oil spillcleanup efforts, which included capping the wellhead and collecting oil, surface combustion, and surface skimming, it was calculated that waste removal, i.e., natural removal of spilled oil, saved BP over 35 billion. This large amount demonstrates the costs of offshore disasters, the importance of the offshore environment to humans, as well as the large monetary values associated with ecosystem services provided.